59 When standard therapy in pregnancy in women with systemic lupus erythematosus and antiphosholipid antibodies is not enough: the global antiphospholipid syndrome score. (April 2019) - Radin, Massimo; Cecchi, Irene; Schreiber, Karen; Rubini, Elena; Roccatello, Dario; Sciascia, Savino
Abstract : Background: Current standard of care (SoC) in pregnancy for patients with Systemic lupus erythematosus (SLE) and/or aPL positivity includes treatment with low dose aspirin (75100 mg/day) and low molecular heparin or unfractionated heparin. However, up to 30% of women continue to have pregnancy complications despite SoC(1). We aimed to assess the validity of the global antiphospholipid syndrome score(GAPSS)(2) in predicting pregnancy morbidity(PM) in patients treated with SoC. Methods: 143 women ever pregnant treated with SoC therapy with SLE and/or aPL positivity were included. Data on cardiovascular risk factors and aPL positivity were retrospectively collected. The individual GAPSS was calculated for each patient by calculating the sum of each risk factor score, as follows: 3 for hyperlipidaemia, 1 for arterial hypertension, 5 for anticardiolipin IgG/IgM, 4 for anti-2glycoprotein I IgG/IgM, 3 for anti-phosphatidylserine/prothrombin antibodies IgG/IgM and 4 for lupus anticoagulant. The patients GAPSS was then grouped according to the patients GAPSS into low risk (<6), medium risk (6-11) and high risk (12). Results: The analysis included 143 patients (mean age 30.8±6.4) with SLE (122;85.3%) and/or aPL positivity, for a total of 352 pregnancies. Overall, we observed a live birth rate of 70.5%, with a total of live birth of 248 out of the 352 pregnancies. Forty-five patients (31%) experienced at least one event of PM, defined as early or late. Patients were stratified according to GAPSS values, in order to identify a low risk group (GAPSS <6, n=72), a medium risk group (GAPSS 6–11, n=66) and a high risk group (GAPSS12, n=5). When considering patients who ever experienced PM while treated with SoC, all patients in the high risk group experienced PM, while patients in the medium group had a significant higher rate of PM when compared to the low risk group [29 (43.9%) patients V.s. 11 (15.3%), respectively; p<0.001]. When analysing the number of pregnancies in the three groups, patients in the high risk group had significantly lower live birth rates, when compared to the other groups [11 (40.7%) life births V.s. 100 (62.1%) and 137 (82.5%), respectively; p<0.05]. Furthermore, patients with medium risk group also had significantly lower live birth rates, when compared to the lower risk group (p<0.001). Figure 1 resumes the results of PM and live births divided in the three groups. Conclusions: GAPSS might be a valuable tool in identifying patients at higher risk of developing any event of PM who might need additional therapeutic approach other than SoC. Funding Source(s): N/A